Projection of storm surge climate extreme over sunda shelf based on IPCC SRES A2 scenario - Wah, Shin How; Halimatun Muhamad; Fredolin T. Tangang; Liew, Juneng (Universiti Kebangsaan Malaysia, 2012)
The historical and future storm surge climate over the South China Sea Sunda Shelf was derived using a barotropic two dimensional model. The atmospheric forcings were obtained from the UKMO regional climate modeling system, PRECIS (Providing Regional Climates for Impacts Studies), forced at the boundary by the ECHAM4 simulation output under the SRES A2 emission experiment. In general, the model simulates historical sea surface elevation characteristics satisfactory although there is a substantial underestimation for the sea level elevation at local scales. The climate change analysis suggests that the storm surge extreme over the Sunda Shelf is expected to increase along the coastal area of the Gulf of Thailand and east coast of Peninsular Malaysia in the future (2071 – 2100). The projected increment is averagely ~9% over the Sunda Shelf region by the end of the 21st century corresponding to about 5% stronger wind speed as compare to the baseline period of 1961-1990.